Proposta de precificação das águas subterrâneas para o uso do polo industrial de Manaus (PIM) - Santos, Izaías Nascimento dos (2018)
The State of Amazonas, in accordance with federal legislation, presents in its State Policy for Water Resources (PERH/AM) the use of raw water, recognizing it as an economic good and contributing to its conscious use. With the installation of the Manaus Free Trade Zone (ZFM), they have greatly affected the quantitative and qualitative water availability of the surface and underground waters of the city of Manaus. The urban pollution of streams through domestic waste and the dilution of treated industrial effluent, as well as the overexploitation of aquifers, which have declined over the last 50 years and, consequently, has seriously compromised the underground resource of this site, causing an imbalance in the balance between the inputs of water in the aquifer (recharge) and the outlets (extraction). In view of this, there is a need for the rational use of waters under state control, with the implementation of administrative, technical and legal regulations in search of management and sustainability of water resources, by those who exercise their legal domain, their users, especially the industrial sector. It is in this context, and in view of its complexity, that this work elaborated a proposal for Groundwater Pricing for the Use of the Industrial Pole of Manaus (PIM) organized in technical criteria based on the volume of water withdrawn and launched in a certain period by its (PPU1-captured and PPU2-dilution), with eleven technical weighting coefficients for capturing and launching effluent, with seven for abstraction: K1 (User type); K2 (Type of use); K3 (Type of source); K4 (Characteristic of the aquifer); K5 (Exploitable reserve); K6 (Class) and K7 (Rainy Seasonality and Density) and four: K1 (User type); K7 (Seasonality-Rainfall and Density); K8 (BOD Efficiency) and K9 (Receiver Body Class). The coefficients are associated to external factors (physical conditions of the region, purpose of use, users and others), and together they made it possible to construct a draft regulation for the regulation of the use of the industrial sector of Manaus, to be submitted to the analysis of the Council State of Water Resources of the Amazon (CERH/AM).